The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.3390/jcm9061681
|View full text |Cite
|
Sign up to set email alerts
|

Functional Heterogeneity of Mouse and Human Brain OPCs: Relevance for Preclinical Studies in Multiple Sclerosis

Abstract: Besides giving rise to oligodendrocytes (the only myelin-forming cell in the Central Nervous System (CNS) in physiological conditions), Oligodendrocyte Precursor Cells (OPCs) are responsible for spontaneous remyelination after a demyelinating lesion. They are present along the mouse and human CNS, both during development and in adulthood, yet how OPC physiological behavior is modified throughout life is not fully understood. The activity of adult human OPCs is still particularly unexplored. Significantly, most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 91 publications
(185 reference statements)
2
35
0
Order By: Relevance
“…Bribián and colleagues [ 3 ] further investigated the differences between the mouse and human adult brain with respect to the respective OPC migratory properties. They showed that murine and human OPCs have similar migratory properties in response to FGF2 and anosmin-1 but differ from that of OPCs taken from early post-natal samples [ 3 ].…”
Section: The Biological Basis Of Cns Remyelinationmentioning
confidence: 99%
See 4 more Smart Citations
“…Bribián and colleagues [ 3 ] further investigated the differences between the mouse and human adult brain with respect to the respective OPC migratory properties. They showed that murine and human OPCs have similar migratory properties in response to FGF2 and anosmin-1 but differ from that of OPCs taken from early post-natal samples [ 3 ].…”
Section: The Biological Basis Of Cns Remyelinationmentioning
confidence: 99%
“…Bribián and colleagues [ 3 ] further investigated the differences between the mouse and human adult brain with respect to the respective OPC migratory properties. They showed that murine and human OPCs have similar migratory properties in response to FGF2 and anosmin-1 but differ from that of OPCs taken from early post-natal samples [ 3 ]. Altogether, these data are consistent with the observation that the markers expressed by oligodendrocyte populations at lesions change according to the inflammatory milieu and support the view that inflammation has important effects on the remyelination capability of OLs.…”
Section: The Biological Basis Of Cns Remyelinationmentioning
confidence: 99%
See 3 more Smart Citations